2020
DOI: 10.1007/s10640-020-00480-7
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of COVID-19 and Other Disasters for Wildlife and Biodiversity

Abstract: We review the economic channels by which the COVID-19 pandemic and subsequent policy responses may affect wildlife and biodiversity. The pandemic is put in the context of more than 5,000 disease outbreaks, natural disasters, recessions and armed conflicts in a sample of 21 high biodiversity countries. The most salient feature of the pandemic is its creation of multiple income shocks to rural and coastal households in biodiverse countries, correlated across sectors of activities and spatially. Various research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The SARS-CoV-2 novel coronavirus (herein called COVID-19 recognizing that this is the resultant disease) pandemic has had an incredibly heavy human toll (from loss of life (Woolf et al, 2020), to mental health crises (Tandon 2020), to loss of livelihoods (Dev 2020), to changes in food security (Uddin et al, 2020)) and rapid and dramatic effects on the world and how it functions. Major changes in human behaviour spanning travel patterns, consumerism, and energy use, among others, have influenced local and global biodiversity (e.g., Gillinghan et al, 2020;Rondeau et al, 2020;Zambrano-Monserrate et al, 2020). These changes define the Anthropocene, a period characterized by unprecedented loss of biodiversity and global environmental change (Steffen et al, 2007), for which there is desperate need for action to stop this loss and restore ecosystems (Jeanson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 novel coronavirus (herein called COVID-19 recognizing that this is the resultant disease) pandemic has had an incredibly heavy human toll (from loss of life (Woolf et al, 2020), to mental health crises (Tandon 2020), to loss of livelihoods (Dev 2020), to changes in food security (Uddin et al, 2020)) and rapid and dramatic effects on the world and how it functions. Major changes in human behaviour spanning travel patterns, consumerism, and energy use, among others, have influenced local and global biodiversity (e.g., Gillinghan et al, 2020;Rondeau et al, 2020;Zambrano-Monserrate et al, 2020). These changes define the Anthropocene, a period characterized by unprecedented loss of biodiversity and global environmental change (Steffen et al, 2007), for which there is desperate need for action to stop this loss and restore ecosystems (Jeanson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, such an effect can be as short-lasting as the length of the lockdowns. Finally, conservation efforts of biodiversity hotspots, especially in developing countries, rely heavily on nature-based tourism that has collapsed, putting at odds conservation enforcement and value for local communities (Rondeau et al 2020 ).…”
Section: Consequences Of Covid-19 Crisis On Sustainabilitymentioning
confidence: 99%
“…The lack of such agendas led to, risingdestruction of the Amazonian rainforest during the lockdown, by 55% in the first four months of 2020 than the same time last year, Caribbean centuries-old coral reefs in Australia were irreversibly damaged due to the lack of treatments against invasive species (e.g., rats that destroy the native species) and fungal diseases on island countries such as New Zealand in the deficiency of extinction efforts (Bang and Khadakkar, 2020). Furthermore, Rondeau et al (2020) reported that the lockdown evaluations have led to financial crises at wildlife Env. Biodiv.…”
Section: Biodiversity During Covid-19mentioning
confidence: 99%